Factors influencing the behavior and challenges faced by visually impaired individuals in waste separation. - Patranit Srijuntrapun; Issavara Sirirungruang (PLoS ONE)
Understanding the behavior and the challenges of visually impaired individuals in waste separation remains a significant research gap that affects the development of an inclusive and sustainable society. This research study aims to identify and analyze the factors influencing the waste separation behavior of visually impaired people and the key obstacles that these individuals face in public spaces. The study uses a quantitative approach, relying on surveys to gather data from a sample of 358 visually impaired individuals through the use of structured questionnaires. The data was then examined using multiple regression analysis. Results revealed that 91.1% possessed a moderate understanding of waste segregation, while 97.7% held generally positive attitudes toward the practice. Approximately 74.9% of the participants actively engaged in waste segregation at a moderate level. Motivation emerged as the most significant influence of proper waste management behavior, alongside attitude and knowledge. However, challenges persist in public settings, where 69.3% of participants discarded waste without regard to bin types, primarily due to difficulties in distinguishing bin colors and general ignorance. To better address their needs, participants recommended practical solutions, such as bins designed to be distinguishable by shape or sound, ensuring a more accessible and inclusive waste segregation system. This research can help in designing targeted interventions that promote sustainable waste management practices for visually impaired individuals. It can also provide valuable information to researchers, practitioners, and policymakers working towards creating inclusive and accessible waste management environments and processes for people with visual impairments.